RESPIRATORY REACTIONS OF THE MERISTEMATIC SYSTEMS OF THE PRIMARY ROOT OF CORN - BALDOVINOS DE LA PENA, GABRIEL (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1942)
Studies on the velocity of respiration and respiratory coeffs were based upon several series of repeated expts on 2 mm segments of 3 zones of primary root tips Endogenous respiratory coeffs after 30 min, 1 hr and 2 hrs, respectively, were, in the
REV SOC MEX HIST NAT
Keywords: RESPIRATORY REACTIONS, MERISTEMATIC SYSTEMS, PRIMARY ROOT, CORN; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL (BOTANICA); FISIOLOGIA VEGETAL